Regeneration of Buccal Wall Defects after Tooth Extraction with Biphasic Calcium Phosphate in Injectable Form vs. Bovine Xenograft: A Randomized Controlled Clinical Trial - Marija Čandrlić; Matej Tomas; Marko Matijević; Željka Perić Kačarević; Marijana Bićanić; Žarko Udiljak; Ivana Butorac Prpić; Ivan Miškulin; Slavko Čandrlić; Aleksandar Včev (MDPI AG, 2023)
Bone healing after tooth extraction may be affected by defects of the alveolus buccal wall, such as fenestrations and dehiscences. Therefore, to minimize dimensional changes it is advisable to perform alveolar ridge preservation after tooth extractions. Different biomaterials are used for this purpose. The aim of this study was to investigate the qualitative and quantitative histological changes in human biopsies taken after 6 months of healing of extraction sockets with buccal wall defects. For this purpose, the defects of 36 patients (18 per group) were treated with injectable biphasic calcium phosphate (I-BCP) or bovine xenograft (BX) after extraction. After six months of healing, biopsies were taken and proceeded to the histology laboratory. No evidence of an inflammatory response of the tissue was observed in the biopsies of either group, and the newly formed bone (NB) was in close contact with the remaining biomaterial (BM). The histomorphometric results showed that there was no statistically significant difference between the groups in the mean percentage of NB (p = 0.854), BM (p = 0.129), and soft tissue (p = 0.094). To conclude, both biomaterials exhibited osteoconductivity and biocompatibility and achieved satisfactory bone regeneration of buccal wall defects after tooth extraction.